The impact of corporate social responsibilities (CSR), entrepreneurship, and financial factors on the financial performance of the banks in ASEAN countries - Nguyen Minh Dat; Nguyen Quang Dai; Pham Bich Ngoc (Contemporary Economics, 2022)
All the organizations are striving for the high financial performance that could influence by many factors and attained the attention of regulators and recent studies. Thus, the present study examined the impact of corporate social responsibilities (CSR), entrepreneurship and financial factors such as leverage and liquidity along with firm size on the financial performance of the banks in ASEAN countries. This study has adopted the quantitative methods for the collecting data and gathered the published secondary data from the statements. The data has been extracted from the financial statements and published CSR reports of the banks in ASEAN countries from 2015 to 2020. The ongoing study has executed the robust standard error and fixed effect model (FEM) to examine the relationships among the variables. The results indicated that CSR, entrepreneurship, leverage, liquidity and firm size have significant and positive nexus with financial performance of the banks in ASEAN countries. These outcomes have provided the guidelines to the regulators of the banks that they should focus on CSR and entrepreneurship that could increase the financial performance of the banks.
Keywords: C33; D22; G21; 330; corporate social responsibilities; entrepreneurship; financial performance; financial factors; leverage; liquidity